2020
DOI: 10.1101/2020.12.10.419184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surprising Phenotypic Diversity of Cancer-associated mutations of Gly 34 in the Histone H3 tail

Abstract: Sequencing of cancer genomes has identified recurrent somatic mutations in histones, termed oncohistones, which are frequently poorly understood. Previously we showed that fission yeast expressing only the H3.3G34R mutant identified in aggressive pediatric glioma had reduced H3K36 trimethylation and acetylation, increased genomic instability and replicative stress, and defective homology-dependent DNA damage repair (Yadav et al., 2017). Here we show that surprisingly distinct phenotypes result from G34V (also … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 69 publications
1
14
1
Order By: Relevance
“…We started with previously established signatures of adult glioblastomas, composed of key effectors of the cell cycle as well as components of crucial DNA repair factors [ 22 ]. Although our data show that the signatures established in aGBMs can indeed capture features related to cell cycle and DNA repair in pHGG tumors, the observed segregation did not correlate with underlying driver mutations affecting histones, as shown in previous studies [ 18 , 20 , 21 , 31 , 32 , 33 ]. Our efforts to identify a specific DNA repair and cell cycle gene expression signature of pHGGs led to a 28-gene expression signature that was able to cluster the sus-tentorial and thalamic pHGG group effectively.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…We started with previously established signatures of adult glioblastomas, composed of key effectors of the cell cycle as well as components of crucial DNA repair factors [ 22 ]. Although our data show that the signatures established in aGBMs can indeed capture features related to cell cycle and DNA repair in pHGG tumors, the observed segregation did not correlate with underlying driver mutations affecting histones, as shown in previous studies [ 18 , 20 , 21 , 31 , 32 , 33 ]. Our efforts to identify a specific DNA repair and cell cycle gene expression signature of pHGGs led to a 28-gene expression signature that was able to cluster the sus-tentorial and thalamic pHGG group effectively.…”
Section: Discussioncontrasting
confidence: 64%
“…Of note, we were able to link histone mutated tumors to a more proliferative group displaying upregulation of the gene components of our signature. Previous studies have shown that the H3.3 G34 mutations impact several aspects of the DDR [ 20 , 21 , 34 ]. Intriguingly, we could not segregate H3.3- and H3.1-mutated DIPG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evidence supporting the involvement of acetylation status of H3K36 in knob formation came from study of a nearby residue in histone H3, H3-G34, which is mutated in pediatric high-grade glioma [ 88 , 89 , 90 , 91 ]. Both histone H3-G34R and H3-G34V mutations led to reduced H3K36me3, accumulation of H3K36me2, and transcriptional repression of ST domains.…”
Section: Specialized Chromatin and Knob Formation On St Domainsmentioning
confidence: 99%
“…Both histone H3-G34R and H3-G34V mutations led to reduced H3K36me3, accumulation of H3K36me2, and transcriptional repression of ST domains. Further, H3-G34R also prevented H3K36 acetylation [ 88 ] and caused an increase in knob formation [ 91 ], whereas H3-G34V did not affect either H3K36 acetylation or knob formation [ 91 ]. These data support the hypothesis that histone H3-G34R induces knob formation through reducing H3K36 acetylation levels.…”
Section: Specialized Chromatin and Knob Formation On St Domainsmentioning
confidence: 99%